The beach club ebook A novel. - Hilderbrand, Elin (2010)
In The Beach Club , the juicy first novel by talented newcomer Elin Hilderbrand, a series of personal dramas are played out during one summer at a Nantucket Beach Club. It's about the love of summer, summer love, and the special feelings we all have for that special summer place—in this case, a hotel and an island. Mack Petersen, manager of the hotel, has been working at The Beach Club for 12 summers. Only this summer is different. His boss, the owner of the hotel, Bill Elliot, shows up in the spring with a new set of demands. His girlfriend Maribel is pressing Mack to get married and Vance, the African-American bellman, who has hated Mack since the day Mack stole his job 12 years ago, threatens him in a deadly scene. Mack knows something's got to give. Love O'Donnell, the new front desk person straight from the slopes of Aspen, is desperately searching for a stranger to father her child. The bellman, Jem Crandall, who posed as Mr. November in his college calendar, is on his way to LA to break into agenting, until he falls in love with Maribel. Emotions are at a peak when a hurricane threatens to wash away The Beach Club and all it stands for. An engrossing, sexy novel that will sweep you away to the beach any time of the year.